Coverage-dependent thermodynamic analysis of the formation of water and hydrogen peroxide on a platinum model catalyst1. Issue 17 (7th May 2015) - de Morais, Rodrigo Ferreira; Franco, Alejandro A.; Sautet, Philippe; Loffreda, David
<x xml:space="preserve">Abstract</x> A DFT-based thermodynamic analysis of the adsorption properties of surface intermediates involved in the formation of water and hydrogen peroxide has been proposed at low and high coverages (353 K and 1 atm).